PENGARUH BUDGETARY GOAL CHARACTERISTICS DAN KEADILAN PROSEDURAL TERHADAP KINERJA MANAJERIAL SATUAN KERJA PERANGKAT DAERAH PROVINSI BENGKULU - Herawansyah, Herawansyah; Fadli, Fadli; Baihaqi, Baihaqi (JURNAL FAIRNESS, 2013)
This research aims to prove the effect of Budgetary Goal Characteristics (BGC) and Prosedural Justice of the government's performance SKPD’s managerial Bengkulu province. This study used a questionnaire to collect the data, the sampling method used in this research is purposive sampling with sample criteria, that is Eslon Officer III and IV at Planning Division or Budget Division. The results indicate that the first hypothesis Budgetary Goal Characteristics (BGC) positive and significant impact on the managerial performance of the government on Bengkulu province. This means that the higher and details Budgetary Goal Characteristics (BGC) will be able to improve the performance of the government on SKPD’s managerial Bengkulu province. Similarly, for the second hypothesis, procedural justice significant and positive effect on managerial performance on SKPD’s. In this case, the higher the level of procedural justice then managerial performance will also be better.